A study on the protection of a whistleblower under the Whistleblower Protection Act 2010 / Aida Shafinaz Ilias, Nabilah Din and Norfatiha Amin - Ilias, Aida Shafinaz; Din, Nabilah; Amin, Norfatiha (2012)
This research examines the protection granted to a whistleblower under the Whistleblower Protection Act 2010 (WPA 2010). The weaknesses in the protection to a whistleblower under the WPA 2010 highlighted the problems in implementing the Act. This research serves as a preliminary study for further research on the protection of whistleblowers.